Bajka profilaktyczna w twórczości studentów pedagogiki opiekuńczo-wychowawczej i profilaktyki (część II) = A preventive fairy tale in the works of graduates of care and prevention pedegogy (part II) - Wawryk, Lidia; Budniak, Marlena; Huculak, Wiktoria; Mleczak, Julia; Szafrańska, Paulina; Sobierańska, Patrycja; Wiśniewska, Sylwia; Żywiczko, Oliwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Positive prevention emphasized in the previous article (part I) emphasizes, among others: supporting the natural potential of young people, their strong skills, telnets, resources. This is also the goal of this article presenting preventive fairy tales of students of bachelor`s studies in Care and Educational Pedagogy and Prevention (full-time and parttime studies), which were created as part of the subject of constructing educational and preventive programs. They concern the prevention of addiction to psychoactive substances - alcohol and drugs, as well as destructive sects - addiction to people`s influence.
Keywords: bajka profilaktyczna; profilaktyka uzależnień; preventive fairy tale; addiction prevention